Scramble for Souls: Scrutinizing the Nature, Growth, and Competing Claims of Ori-Oke in Ilorin, Nigeria - Nwosu, Patrick U.; Odeh, Lemuel E.; Alamu, Akiti G.; Mohammed, A. Y. (International Bulletin of Mission Research, 2017)
This article examines the evolution of Ori-Oke (Yoruba term for prayer mountain) as a religious phenomenon in Ilorin, Nigeria. Based on the participatory spirituality theory of J. N. Ferrer, the article discusses the impact of Ori-Oke on people’s daily life and how its spirituality strives to provide satisfying answers to the deepest questions of human existence. It highlights the characteristics of Ori-Oke spirituality and prayer formats. The article concludes with reflections on the reasons Ori-Oke is trending and the future it holds for peaceful coexistence and dialogue among religions in Nigeria.
free
Keywords: Culture and Christianity; Nigeria.; Orishas; Prayer – African religion; Spiritual life (Christianity); Yoruba (African people) – Religion